Performance On Digital Dramaturgy Regionin Simultaneous Video Conferences - Sepang, Nurul Robbi; Agustin, Sari Monik (UI Scholars Hub, 2021)
Pandemic has forced us to work and learn from home. Data shows a significant increase in internet usage during the pandemic. People have longer working time, online meetings and sometimes they have to do several meetings at the same time (simultaneously). Then, how do you make a presentation when it has to be fragmented? This paper aimed to identify how you perform digital dramaturgy through simultaneous video conference. The frame of reference was built using Goffman’s Dramaturgy and Mead’s Self. The study was carried out under the construction paradigm and data were collected from observations and interviews with educators who carried out teaching and learning through zoom and g-meet. The results show that digital dramaturgy appears in backstage preparation and front-stage performances. The interesting finding is when there is a simultaneous meeting, the Self appears on the front stage where the camera and the mic are on, but the Self is also on the back stage when the video camera and mic are off. Then, the third situation, which I call In-between Region, appears when part of the Self appears on the front stage, but other parts appear on the back stage. Pandemi memaksa kita melakukan aktivitas bekerja dan belajar dari rumah. Data menunjukkan peningkatan signifikan pemakaian internet di masa pandemic. Waktu kerja yang lebih lama, rapat-rapat daring dan kadangkala dilakukan di saat yang bersamaan (simultan). Lalu bagaimana Diri melakukan presentasi ketika harus ter-fragmentasi? Tulisan ini bertujuan mengidentifikasi bagaimana Diri melakukan dramaturgi digital melalui konferensi video yang simultan. Kerangka pemikiran dibangun menggunakan Dramaturgi Goffman dan Diri dari Mead, dengan menggunakan paradigma konstruksivis dan observasi serta wawancara dalam pengumpulan datanya pada pendidik yang melakukan pengajaran melalui zoom dan g-meet. Hasil penelitian menunjukkan dramaturgi digital muncul dalam persiapan di belakang panggung dan penampilan di panggung depan. Temuan menariknya adalah ketika terjadi pertemuan simultan, Diri muncul di panggung depan dalam keadaan kamera menyala dan posisi mic menyala, namun Diri juga berada di panggung belakang ketika kamera video dan mic mati. Lalu, situasi ketiga, yang peneliti namakan In-between Region muncul, yaitu ketika Sebagian Diri muncul di panggung depan, namun sebagian lainnya muncul di panggung belakang.